Implementasi Model Pembelajaran PAUD Berbasis Sentra dan Waktu Lingkaran dalam Meningkatkan Berbagai Aspek Perkembangan Anak - Wilis Werdiningsih (Southeast Asian Journal of Islamic Education Management, 2022)
Early childhood education (PAUD) is an important stage for a child's early development. PAUD has a goal to facilitate the growth and development of children in a more measurable and comprehensive manner. A conducive environment in PAUD institutions has a positive impact on children's development. There are various kinds of learning models in early childhood, one of which is the center learning model and circle time (Beyond Centers and Circle Time/BCCT). The center learning model and the circle time or commonly referred to as the center model, is a model for implementing PAUD that focuses on children, which in the learning process is centered in the play center and uses four types of footings to support children's development. Therefore, in learning centers it is necessary to prepare for a center class and various equipment that supports learning activities in each center class. This study aims to explore in greater depth the implementation of the center-based PAUD learning model and circle time. The approach used in this study is a qualitative approach. Data obtained from interviews, observations, documentation and supported by various references related to the learning center model. The results show that the learning center model is one of the learning models that can increase student activity in learning activities, as well as improve various aspects of child development, including aspects of religious and moral values, physical-motor, cognitive, language, social-emotional, and artistic aspects.   Keywords: PAUD learning model, BCCT/central class, aspects of child development.